Application of Nonlinear Programming to Heat Conduction Model - Zhe Zhang; Yingzhen Wang; Wenyuan Sun (International Journal of Engineering and Management Research, 2018)
The design of high-temperature working clothes is a process of theoretical analysis and design of all layers of working clothes based on the premise that human body avoids burns under the high-temperature environment. Steady temperature mathematical model in this paper, through the establishment of system, determine the optimal heat work suit II layer thickness is actually an optimization problem, has been the function relation between the temperature and time conditions, through Fourier heat conduction law, obtained the system ultimately a function of temperature and material thickness, and has set up a nonlinear programming problem, the introduction of the simulated annealing algorithm, and joined the convection and radiation in the algorithm the two factors affect the optimal solution, finally satisfied under the condition of the optimal thickness of the second floor.